Factors That Influence Customers Uptake of Bancassurance Products in Kenya - Mburia, Douglas Mugendi (My University, 2012)
The purpose of this study was to determine the factors that influence retail bank customers to buy insurance products from commercial banks. The specific objectives were to establish how consumer awareness influence the decision to buy insurance products from commercial banks, establish whether product type has an influence on retail bank customers’ decision to buy insurance products from commercial banks, to establish the effect of customer care on the customers’ decision to buy insurance products from commercial banks and to identify the influence of consumer attitude on retail bank customers’ decision to buy insurance products from commercial banks. The study adopted a descriptive research design in which all the customers of the 8 commercial banks doing bancassurance were targeted. The study used disproportionate stratified sampling to select respondents from the sampled banks, hence a sample size of 385 respondents. Data was collected by use of questionnaires which was self administered by the researcher. Descriptive statistics was used to analyze the data. The study employed ordinary least squares to determine the relationship between the variables. The study established that awareness of insurance products does not influence the decision of customers to purchase. The respondents were satisfied with the services they received from the banks and would recommend their friends to the bank. The study established that the respondents had a positive attitude towards the bank selling insurance products, the customers therefore trusted the banks selling insurance products. Majority of the respondents bought insurance products from banks which included agriculture/livestock, auto and personal accident insurance policies. The type of products sold by the banks influenced the decision to buy the insurance products from the bank. The study recommended that commercial banks should engage in more awareness to sensitize consumers on the insurance products they are selling. The study further recommended that banks adopt strategies that will enhance customer satisfaction. Finally, the study recommended that banks improve their skills in understanding and handling the insurance products.